A PALLIATIVE CARE EDUCATION IN ASSISTED LIVING PROGRAM TO IMPROVE ADVANCE CARE PLANNING DISCUSSIONS. (11th November 2018) - Dobbs, D J; Hyer, K; Meng, H; Haley, W; Fanfan, D
Abstract: Close to 300, 000 older adults with serious illness die in assisted living (AL) communities. AL administrators have indicated there is a strong need for education for nursing staff about issues related to end-of-life care, particularly related to advance care planning (ACP). A structured palliative care education program that included a session on ACP was piloted in a sample of residents (N=29) and licensed nurses (N=17) from three Florida AL communities to test if it increased documentation of ACP discussions. The resident sample had to be hospice eligible but not receiving hospice. The majority of residents (86%) had advanced dementia. Findings indicated more documentation of ACP discussions in the two treatment ALs compared to the control AL, with a slight increase from baseline to three months. ACP treatment protocols developed for AL staff will be presented as a tool to improve ACP discussions among staff, families and residents.